Фотореакції макроциклічних сполук на поверхні вюрциту (1010) – взаємовплив конформації та електронних ефектів - Golovanova, V. V.; Nazarchuk, B. V.; Postnyi, O. V.; Rantala, T. T.; Tkachenko, N. V.; Golovanov, V. V. (Publishing house "Academperiodika", 2019)
Macrocyclic dyes such as phthalocyanine and porphyrin molecules are modeled on (1010) wurzite surfaces using the DFT and molecular dynamics approaches. It is found that the single dye anchored on the wurtzite surface stabilizes in an inclined geometry with its core facing the surface at a tilting angle of ca 60∘. The tilting of the dye relative to the crystal surface has a dual effect on the charge transfer from a chromophore to the semiconductor. Increasing the tilting angle leads to a stronger coupling between the lowest level of the semiconductor conduction band and dye’s LUMO, thus raising the tunneling probability of the electron injection. By contrast, the electrostatic interaction between units upon the tilting of macrocycles results in a lowering of the molecule LUMO level with respect to the conduction band minimum of the wurzite crystal, which may hinder the electron transfer. The type of a linker and peripheral substituents significantly affect the mutual conformation of the moieties, and their proper choice can facilitate the photoinduced charge transfer reactions.